2023
DOI: 10.1111/jipb.13467
|View full text |Cite
|
Sign up to set email alerts
|

The alleviation of ammonium toxicity in plants

Abstract: Nitrogen (N) is an essential macronutrient for plants and profoundly affects crop yields and qualities. Ammonium (NH4+) and nitrate (NO3−) are major inorganic N forms absorbed by plants from the surrounding environments. Intriguingly, NH4+ is usually toxic to plants when it serves as the sole or dominant N source. It is thus important for plants to coordinate the utilization of NH4+ and the alleviation of NH4+ toxicity. To fully decipher the molecular mechanisms underlying how plants minimize NH4+ toxicity may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…However, excessive NH 4 + is harmful to plant growth and leads to life-threatening conditions, so part of NH 4 + produced by reducing NO 3 – must be absorbed through the joint catalytic abilities of GS and GOGAT . Meanwhile, GDH is also an important pathway in rapid NH 4 + assimilation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, excessive NH 4 + is harmful to plant growth and leads to life-threatening conditions, so part of NH 4 + produced by reducing NO 3 – must be absorbed through the joint catalytic abilities of GS and GOGAT . Meanwhile, GDH is also an important pathway in rapid NH 4 + assimilation .…”
Section: Discussionmentioning
confidence: 99%
“…29 Meanwhile, GDH is also an important pathway in rapid NH 4 + assimilation. 29 This study found drought remarkably activated GS and GOGAT activities, but inhibited GDH activity, also upregulated the expression level of the gene (Glyur000722s00018853) encoding GS in G. uralensis, which suggests that drought caused the declined accumulation of NH 4 + primarily by accelerating assimilation of NH 4 + to Glu through GS/GOGAT pathway, thus accompanied by the increased Glu accumulation. Interestingly, G5 or/and Si significantly increased the NH 4 + content and GDH activity but decreased the GS and GOGAT activities in drought-stressed G. uralensis.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…After entering plant cells, NH 4 + is rapidly converted to glutamine and glutamate via the GS-GOGAT-GDH cycle ( Xiao et al., 2023 ). Our study observed a significant increase in the activities of GS/Fe-GOGAT, NADH-GDH, and NAD + -GDH in the roots of both wheat cultivars under NH 4 + stress ( Figures 7A–D ), further evidencing the activation of NH 4 + assimilation-associated enzymes in wheat seedlings by NH 4 + stress ( Setién et al., 2013 ; González-Moro et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the toxicity of ammonia. On the one hand, the nitrogen in the fertilizer used in the experiment was ammonium N, and the excess ammonium N may produce ammonia toxicity to inhibit plant growth [42,43]; on the other hand, biochar may have inhibited nitrification, which may further enhance the toxicity of ammonia [44,45]. In addition, with the reduction in N application, the ammonia toxicity will diminish so that plant growth will not be inhibited.…”
Section: Discussionmentioning
confidence: 99%